Circulating Levels of Betatrophin and Irisin Are Not Associated with Pancreatic β-Cell Function in Previously Diagnosed Type 2 Diabetes Mellitus Patients - Lingshu Wang; Jun Song; Chuan Wang; Peng Lin; Kai Liang; Yu Sun; Tianyi He; Wenjuan Li; Ruxing Zhao; Jun Qin; Yiran Lu; Jinbo Liu; et al. (Journal of Diabetes Research)
Betatrophin and irisin are two recently identified hormones which may participate in regulating pancreatic β-cell function. However, the associations of these two hormones with β-cell function remain unclear. The present study aims to demonstrate the associations of circulating betatrophin and irisin levels with β-cell function, assessed by the area under the curve (AUC) of C-peptide, and the possible correlation between these two hormones in previously diagnosed type 2 diabetes mellitus (T2DM) patients. In total, 20 age-, sex-, and body mass index- (BMI-) matched normal glucose tolerance (NGT) subjects and 120 previously diagnosed T2DM patients were included in this study. Partial correlation analysis was used to evaluate the relationships between these two hormones and indexes of β-cell function and insulin resistance. Our results showed that betatrophin levels were significantly elevated, while irisin levels were significantly decreased, in patients with T2DM compared with NGT subjects. However, partial correlation analysis showed that betatrophin levels did not correlate with β-cell function-related variables or insulin resistance-related variables before or after controlling multiple covariates, while irisin correlated positively with insulin sensitivity but is not associated with β-cell function-related variables. Besides, no correlation was observed between betatrophin and irisin levels. Hence we concluded that betatrophin and irisin were not associated with β-cell function in previously diagnosed T2DM patients.